The Influence of the Team Games Tournament (TGT) Learning Model on the Participation Level of Santri in Fiqh Subjects In Islamic Boarding Schools - Tia Andesti; Jamaris Jamna (Universitas Negeri Padang, 2021)
This study aims to see the effect of the Teams Games Tournament (TGT) cooperative learning model on the learning participation of students in Islamic Civilization History subjects. This research is motivated by a less varied learning model in the subjects of Islamic Civilization History. This type of research is quantitative with quasi-experimental methods and a non-equivalent control group design. The research subjects used two classes, namely the experimental and control classes, which then used an instrument in the form of an observation sheet. Data analysis to test the effectiveness of learning using the t test. The results showed that the participation rate of students in the experimental class was in the high category with a mean of 18.40 (77%) while the control class was included in the fairly high category of 14.00 (58%). Participation in learning can also improve students 'understanding, it can be obtained from the results of the students' Post Test. The results of hypothesis testing by applying the Independent Sample T Test, it is known that the value (Sig 2-tailet) is 0,000 and less than 0.05, so it can be concluded that the Team Games Tournament (TGT) method can increase the participation of students.Keywords: Team Games Tournament (TGT), Participation, Learning